UJI BEDA TINGKAT KESEHATAN BANK ANTARA PERBANKAN SYARIAH INDONESIA DENGAN PERBANKAN SYARIAH MALAYSIA - Adytya Ratna Puspita; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2019)
This research aims to determine the difference of Bank Financial Soundness between Indonesia Sharia Banks and Malaysia Sharia Banks during the period of 2012-2016. This research used RGEC method (risk, good corporate governance, earning, capital) to analyze the bank soundness using six financial ratios such as, FDR, NPF, BOPO, ROA, ROE and CAR. The data of this research was using financial report which were provided by each sharia bank. The sample of this research is limited only for sharia commercial banks totally 21 banks which is consist of 11 sharia commercial banks in Indonesia and 10 sharia commercial banks in Malaysia. Test of the data normality was using Kolmogorov-Smirnov Test, while to find out the condition of each variable was using descriptive statistic and Mann-Whitney U Test for hypothesis testing. All research indicators showed that there’s the differences of FDR, NPF, BOPO, and ROE between sharia commercial banks in Indonesia and Malaysia. While the other two variables such as ROA and CAR showed that there’s no the differences between sharia commercial banks in Indonesia and Malaysia.